Correction methods for noncontact intraocular pressure measurement in patients with keratoconus and healthy individuals - Alvani,Azam (2022)
ABSTRACT Purpose: The objective of this study was to investigate the usefulness of four different algorithms to correct noncontact intraocular pressure measurement errors in keratoconus patients and normal individuals. Methods: Noncorrected intraocular pressure and corrected intraocular pressures were measured in one eye of 34 patients with keratoconus and 34 age- and gender-matched healthy controls using Corvis Scheimpflug Technology. The correlation of noncorrected intraocular pressure and corrected intraocular pressures with age, axial length, corneal shape, thickness, and biomechanics was calculated. Corrected intraocular pressures were compared with noncorrected intraocular pressure using paired t test and Bland-Altman plots (95% limits of agreement). Results: The noncorrected intraocular pressure correlated with corneal thickness and biomechanical parameters in both groups (all p≤0.047), and front and back mean keratometry in the keratoconus group (r=-0.39, p=0.02, and r=0.39, p=0.02, respectively). After adjustment with different intraocular pressure correction algorithms, biomechanically corrected intraocular pressure showed a minimal correlation with corneal features and a nonsignificant difference with noncorrected intraocular pressure in the healthy group (-0.1 ± 1.1 mmHg, p=0.58; 95% limits of agreement: -2.3 to 2.1 mmHg). Conclusions: Measuring intraocular pressure using noncontact tonometry and its corrected forms with a corneal thickness-based simple linear formula in patients with keratoconus is associated with many errors. Using more complex formulas that take into consideration more corneal stiffness parameters in addition to corneal thickness, such as biomechanically corrected intraocular pressure formula, may be more reliable and beneficial in this group of patients.